Pengaruh Cahaya Artifisial terhadap Karakter Morfologi dan Genetik Bacopa caroliniana dalam Kultur Jaringan - Syakhril Alam; Laela Sari; Nonon Saribanon; Wening Enggarini; Nurhamidar Rahman; Evan Maulana; Amalia Prihaningsih (Vegetalika, 2025)
Bacopa caroliniana has great potential in the fields of ecology, medicinal and ornamental, also has aesthetic value in the form of very rare small blue flowers. This beauty is highly sought after among aquatic lovers, for that genetic diversity is needed using the light spectrum. However, understanding of the influence of light spectrum on the growth and genetic characters of B. caroliniana using tissue culture. The research was carried out from March 2023 to January 2024 at the KST Soekarno National Research and Innovation Agency Laboratory, Cibinong, Bogor. Explants were grown in MS media (Murashige and Skoog) treated with white (control), blue, red and purple LED light. The design used in this research was a Completely Randomized Design (CRD) with one factor and six replications. Observations include plant height, number of leaves, number of axillary shoots, number of roots, as well as genetic analysis through DNA extraction, PCR and sequencing. The results showed that white light gave the best results on all morphological parameters, with the highest number of leaves (30,800), while purple light produced the lowest number of leaves (17,500). The ANOVA test showed that plant height did not differ significantly between treatments (Sig. = 0.137), indicating the adaptability of B. caroliniana to various light spectra. The research conclusions show that white light is optimal for increasing leaf number and photosynthetic capacity, which is highly relevant in tissu culture and aquaculture applications. Genetically, blue and white light treatment did not cause significant genetic changes, while red and purple light showed slight, temporary genetic changes, possibly influenced by epigenetic mechanisms.